Improving management practices and clinical outcomes in type 2 diabetes study: Prevalence of complications in people with type 2 diabetes in India - Ashok Kumar Das; V Seshiah; B K Sahay; A Kumar; A J Asirvatham; V Balaji; S Kalra; R Channabasavaiah; R Shetty; C. R. A. Moses (Indian Journal of Endocrinology and Metabolism, 2012)
Introduction: Diabetes is the fourth leading cause of disease-related death and almost 80% of diabetes-related deaths occur in developing countries. Optimal glycemic control, in particular HbA1c level less than 7% with effective management of dyslipidemia and hypertension can reduce development of diabetes-related complications. Delay in initiating/or optimizing appropriate anti-diabetic therapy including insulin could be a possible cause of the increase in complications. Method: Improving management practices and clinical outcomes in type 2 diabetes (IMPACT) was a prospective, open-label, 26-week, comparative, multi-center study to compare efficacy and safety of the Indian insulin guideline (IIG) group versus routine clinical practice (RCP) group in type 2 diabetes patients. A total of 20,653 subjects from 885 centers across India were enrolled. Results: A total of 4695 patients (22.7%) (IIG, 4113 [22.6%]; RCP, 582 [23.5%]) had macrovascular complications and 8640 patients (41.8%) (IIG, 7486 [41.2%]; RCP, 1154 [46.6%]) had microvascular complications. Of 4695 patients with macrovascular complications, 2850 patients (60.7%) had coronary heart disease followed by 1457 patients (31.0%) with peripheral vascular disease. Of all the microvascular complications recorded, 5627 patients (65.1%) had peripheral neuropathy followed by 3313 patients (38.3%) with retinopathy. Conclusion: The rates of complications were high in patients with type 2 diabetes at the time of being initiated on insulin therapy in India.